2022
DOI: 10.1093/ndt/gfac029
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone and phosphate homeostasis in patients with Bartter and Gitelman syndrome: an international cross-sectional study

Abstract: Background Small cohort studies have reported high parathyroid hormone (PTH) levels in patients with Bartter syndrome and lower serum phosphate levels have anecdotally been reported in patients with Gitelman syndrome. In this cross-sectional study, we assessed PTH and phosphate homeostasis in a large cohort of patients with salt-losing tubulopathies. Methods Clinical and laboratory data of 589 patients with Bartter and Gitelm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…15 They also reported that there was no correlation between PTH levels and urinary calcium excretion, which is usually high in type 1 and type 2 BS patients. 15 In some papers, it is discussed that hypokalaemia and high prostaglandin E2 levels may contribute to PTH resistance. 13,16 However, the details of why patients with type 1 and type 2 BS exhibit PTH resistance are largely unknown.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…15 They also reported that there was no correlation between PTH levels and urinary calcium excretion, which is usually high in type 1 and type 2 BS patients. 15 In some papers, it is discussed that hypokalaemia and high prostaglandin E2 levels may contribute to PTH resistance. 13,16 However, the details of why patients with type 1 and type 2 BS exhibit PTH resistance are largely unknown.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, Verploegen et al analysed biological data from hundreds of patients with BS and Gitelman syndrome. They found that patients with type 1 BS and type 2 BS had significantly higher PTH levels than those with other types of BS and Gitelman syndrome 15 . They also reported that there was no correlation between PTH levels and urinary calcium excretion, which is usually high in type 1 and type 2 BS patients 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In-depth phenotyping of Gitelman patients with SLC12A3 mutations has resulted in the identification of subclinical phenotypes [5,20 ▪ ]. In a large European cohort, 20% of patients with Gitelman syndrome had hypoparathyroidism [20 ▪ ].…”
Section: Slc12a3 – Classic Gitelmanmentioning
confidence: 99%
“…In-depth phenotyping of Gitelman patients with SLC12A3 mutations has resulted in the identification of subclinical phenotypes [5,20 ▪ ]. In a large European cohort, 20% of patients with Gitelman syndrome had hypoparathyroidism [20 ▪ ]. As the parathyroid harmone (PTH) and magnesium concentrations were correlated in this cohort, it has been hypothesized that the hypoparathyroidism is explained by Mg 2+ -dependent regulation of the calcium-sensing receptor [21].…”
Section: Slc12a3 – Classic Gitelmanmentioning
confidence: 99%